CONTEMPORARY HISTORICAL ANALYSIS ON LEGITIMACY OF â€œSUICIDE ATTACKSâ€ AS A METHOD OF WAR - Arpa, Enver (Journal of Al-Tamaddun, 2019)
In this article, suicide bombings which have been resorted to by various organizations in our day and accepted by some religious groups as martyrdom (istishhad) activities have been examined in terms of religion. For this purpose, it is focused in this article on such issues as when and how this type of action that has caused a great upsurge in the whole world has begun to spread and become widespread, the structure of thought of organizations that use it, when and for what reasons the religiously qualified groups began to refer to these actions, its place in Islam and so on. In this framework, the evidence of those who defend the legitimacy of this action and those who forbid it have been evaluated. Then, it is analyzed how Abu al-Abdullah al-Muhajir, one of the spiritual guides of the jihadist Salafi mentality who regarded these attacks as an important element of his concept of jihad and transformed it into a military strategy for his struggle, justified this action, in his book (Masail min Fiqh al-Jihad), in terms of religion, especially whether the evidence or reasons he put forward from the Quran and the Sunnah are healthy, and they are analyzed in light of basic Islamic sources using descriptive analysis methodology. It has been concluded that Islam, which regards peace and justice as its basic principles and assures human security of property and life, is not possible to find such an action acceptable that could cost lives of innocent people.